COVID-19 and Pregnancy: A Review - Singh, Pratibha; Goyal, Manu; Singh, Kuldeep; Misra, Sanjeev (Annals of the National Academy of Medical Sciences (India), 2020)
Novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has affected the lives of people across the globe, and Obstetricians are studying its effect on pregnancy and newborns. The pandemic resulted in major decisions taken by leaders in many countries, including strict policies as laying down of compulsory lockdown, curfews in high-risk places, and shut down of many services. This was done to promote physical distancing, thereby preventing community spread of the virus and for the preparedness of the health care facilities to deal with the pandemic. In the current scenario, the pregnant women who want to seek antenatal care are unable to visit the clinician and health center due to lockdown or for fear of contracting an infection. Reduced antenatal visits might lead to missing out some high-risk factors in due course of pregnancy and has the potential to adversely affect the health of women and newborn. Some key issues like optimizing antenatal and intranatal care with the prevailing situation, the effect of COVID-19 infection on fetus and newborn are addressed here. We searched PubMed (National Library of Medicine) and Embase (Elsevier) databases from January till July 2020, using a combination of the following keywords: “COVID-19,” “SARS-CoV-2,” and “pregnancy.” Studies were selected if they met the following criteria: clinical studies, studies reporting original data, studies reporting SARS-CoV-2 infected women who were pregnant or had delivered. Here, we are providing the consensus made from the available literature. There is not much effect of COVID-19 infection on mother and fetus. The vertical transmission of the virus is also not yet proven. The timing and mode of delivery are not affected by the COVID-19 infection to the mother. Obstetric treatment should not be delayed for the COVID-19 testing or report. There are only a few studies reported for the management of pregnant women during pregnancy, based on which some principles formulated. However, more extensive studies are required to validate these principles. This review briefly describes the precautions needed to take during antenatal care.
Keywords: COVID-19 in pregnancy; SARS-CoV-2 infection in pregnancy; coronavirus infection in pregnancy